Neuroticism and extraversion are modifiable by treatment in individuals at-risk for psychosis or with first-episode psychotic disorder - Boyette, Lindy-Lou; Schirmbeck, Frederike; Vermeulen, Jentien M.; van der Ven, Els; van Aubel, Evelyne; Vaessen, Thomas; Beijer-Klippel, Annelie; Batink, Tim; van Winkel, Ruud; van der Gaag, Mark; de Haan, Lieuwe; Reininghaus, Ulrich; et al. (Personality and individual differences, 2024)
Meta-analytic work suggests that Neuroticism and Extraversion levels are modifiable by treatment, but it is unknown whether this holds for individuals with subclinical or clinical psychosis. The current study aimed to examine whether 1) Neuroticism and Extraversion change through intervention in individuals at clinical high risk for psychosis (CHR) or first-episode psychosis (FEP), and 2) Acceptance and Commitment Therapy in Daily Life (ACT-DL) is more successful in this regard compared to treatment as usual (TAU). Data pertain to the INTERACT study, a randomized controlled trial on the efficacy of ACT-DL in individuals with CHR or FEP. Assessments were at baseline, 8 week post-intervention and 6 and 12-month follow-up. Our sample consisted of 142 participants (ACT-DL: 67 and TAU: 75). Mixed model analyses showed a reduction in Neuroticism at post-intervention and both follow-up. Extraversion increased at 6 month follow-up. There was no difference between ACT-DL and TAU in personality change. Analyses were controlled for clinical group status (CHR vs. FEP), gender, age, IQ, baseline personality levels and baseline symptom levels. Our findings suggest that among help-seeking people at-risk for psychosis or with first-episode psychosis, treatment may have a fast and persistent impact on particularly Neuroticism. Potential mechanisms are discussed.
Gesehen am 08.01.2024